Occurrence and molecular characterization of Echinococcus granulosus in Turkish mouflon (Ovis gmelinii anatolica) - Simsek, Sami; Eroksuz, Yesari (Elsevier, 2009)
This report presents a case of Echinococcus granulosus infection in a Turkish mouflon (Ovis gmelinii anatolica) The mouflon was found dead and postmortem examination was conducted. The diagnosis of liver hydatid cyst was established by pathological and molecular findings. For the purpose of the molecular characterization of cyst material, mitochondrial cytochrome oxidase subunite 1 (mt-CO1) gene region was amplified and sequence analyses were carried Out. Sequence corresponding to mt-CO1 gene was identical to a sequence reported for common sheep strain (G1). This is the first report of an occurrence and molecular characterization of E. granulosus in Turkish mouflon. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Echinococcus granulosus; Mouflon; Genotyping; Turkey